IMPROVING VERTICAL MILLING ADAPTER FOR STRIP TILLAGE - Прасолов, Є. Я.; Бєловол, С. А.; Бєловол, Ю. Ю.; Мацаков, А. В. (Scientific Progress & Innovations, 2017)
The article presents an analysis of existing technologies, machinery construction and working parts for pre-treatment of the soil; expediency of terraced cultivation technologies in the Forest-Steppe zone of Ukraine; we identified promising areas of improvement tillers. For the offered technical solutions of vertical milling adapter we determined optimal performance of the kinematic mode and the number of work items, which guarantees evenness of tillage. The introduction of vertical milling adapter of offered design with reasonable parameters provides a high quality and uniformity of treatment of the working area, effectively loosening the soil, leveling the profile of the bottom of the furrow and the treated surface with rational energy intensity and efficiency of the process.